(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The explosion of the Covid-19 pandemic has led us to introduce numerous states of exception in our everyday lives, sparking debates about their appropriateness at various levels. Among other changes we have adopted, there has been an increase of apps supporting our fight against Covid-19 all over the world. From apps helping us to join and coordinate clinical trials to contact tracing apps, various are the instances in which digital technology has -at least attempted to- come to rescue to the scientific, public policy and political realms during the challenging times we are currently living in. Particularly in relation to contact tracing apps, ethical concerns have been raised over the level of transparency that they can guarantee, often stressing how the State needs to ensure a number of variables to be granted to citizens: from privacy to fairness of access and distribution through their compulsory status or not. In Western liberal democracies, the assumption has been that all risks associated with this digital technology would have to be dealt with by the State -hence making its misuse "only" public, albeit authoritarian in their most dystopian versions. Here, the intention is to stress some of the overlooked dimensions of the use of different types of Covid-19 related apps. More specifically, this paper takes issue with the secondary use of data that various private companies engaged in the fight against Covid-19 could make -with an unclear role for informed consent. Especially when in the hands of private, for profit, companies, attention should abound on what states of exceptions we are allowing to slip through our ethical supervision -and to what we are actually giving consent to when downloading these apps.